2012
DOI: 10.1007/s10753-012-9495-9
|View full text |Cite
|
Sign up to set email alerts
|

Imperatorin Attenuates LPS-Induced Inflammation by Suppressing NF-κB and MAPKs Activation in RAW 264.7 Macrophages

Abstract: Imperatorin is a type of coumarin compound with antibacterial and antiviral activities. In the present study, we examined the anti-inflammatory effects of imperatorin in lipopolysaccharide (LPS)-stimulated RAW 264.7 macrophages by investigating its impact on the production and expression of cytokines and the major signal-transduction pathways. We found that imperatorin downregulated LPS-induced levels of TNF-α, IL-1β, and IL-6 in RAW 264.7 macrophages in a concentration-dependent manner, and it significantly i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(41 citation statements)
references
References 29 publications
1
38
2
Order By: Relevance
“…It has been reported that three flavonoids (naringin, neoponcirin and poncirin) and three coumarins (umbelliferone, imperatorin and auraptene) isolated from the 70% ethanolic extract of Ponciri fructus have various pharmacological actions including antioxidant [27], anxiolytic-like [28], anticancer [29], and anti-inflammatory effects [30][31][32]. Therefore, we propose that PFE can have antiproliferative and antioxidant effects based on the various pharmacological activities of the chemical-chemical interactions on the development and progression of lesions in a TP-induced model of BPH.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that three flavonoids (naringin, neoponcirin and poncirin) and three coumarins (umbelliferone, imperatorin and auraptene) isolated from the 70% ethanolic extract of Ponciri fructus have various pharmacological actions including antioxidant [27], anxiolytic-like [28], anticancer [29], and anti-inflammatory effects [30][31][32]. Therefore, we propose that PFE can have antiproliferative and antioxidant effects based on the various pharmacological activities of the chemical-chemical interactions on the development and progression of lesions in a TP-induced model of BPH.…”
Section: Discussionmentioning
confidence: 99%
“…This was in line with results published about the substances imperatorin and roxatidine, which inhibit LPS-induced p38 but not Erk activity in RAW 264.7 macrophages. These substances were shown to downregulate TNF-α and IL-6 production in LPS-stimulated macrophages, implying dispensability for the Erk pathway in this respect [42, 43]. Interestingly, TACE-mediated processing of pre-TNF was demonstrated to be dependent on Erk signaling in LPS-stimulated macrophages [44], indicating cell type-specific regulation of TNF-α production.…”
Section: Discussionmentioning
confidence: 99%
“…After adding LPS, the amount of NO was increased in peritoneal macrophages, yet it was decreased in ethanolstimulated GES-1 cells. It is, therefore, suggested that LPS can bind to the cell membrane receptor of the monocytes/macrophages and endothelial cells so as to activate the signal-transduction system, thus resulting in the synthesis and release of cytokines and inflammatory mediators such as the over expression of iNOS (Guo et al 2012). On the contrary, the expression of cNOS in gastric mucosa cells was reduced significantly after ethanol injury, showing that endogenous NO played an important role in acute gastric injury caused by ethanol.…”
Section: Discussionmentioning
confidence: 99%